FUNGSI RITUAL GENDHING TOLAK BALAK PADA PERTUNJUKAN JARANAN KRIDHA BUDAYA DI KABUPATEN TRENGGALEK - Rika Wahyuningtyas; Muhammad Nur Salim (Surakarta: Jurusan Karawitan Institut Seni Indonesia Surakarta, 2021)
The research started from an interest in ritual phenomena in the Jaranan Kridha Budaya performance. The Ritual of Rejection is defined as a means to convey a special message to God Almighty so as not to bring down calamities, such as natural disasters and disease outbreaks. In the Obong Incense ritual, it is required to use the Reject Balak Gendhing which is a mandatory gending and cannot be replaced with another gending. Gendhing Tolak Balak is a gending that is believed to have a religious ritual function in the Art of Jaranan Kridha Budaya when the Obong Incense Ritual is served. Gendhing Tolak Balak is used as a standard gending which is interpreted as a means to submit a request, or as a form of indirect interaction with God and the dancers of a place. The relationship between the components of gending and ritual, creates a sacred impression and influences the actors and their supporting communities.